Barriers in Proper Maternal Referral Systems: A Scoping Review of Qualitative Research - Dedeh Supriyatin; Khusnul Khotimah; Qorinah Estiningtyas Sakilah Adnani; Bibek Giri (JURNAL INFO KESEHATAN, 2025)
The maternal referral system is a crucial component of healthcare services designed to ensure the welfare of women and babies throughout pregnancy, delivery, and the postpartum phase. This method allows pregnant women with complications to get improved and specialized healthcare treatments in adequately equipped and skilled maternity facilities. However, the effectiveness of maternal referral systems is sometimes hindered by several complex and interrelated concerns, especially in resource-limited countries. This research seeks to examine barriers in the maternal referral system. This study utilizes a scoping review of qualitative research techniques to analyze the PEO framework. The P (Population) component examines the attributes of pregnant women and healthcare professionals engaged in the maternal referral system. The E (Exposure) component examines the obstacles faced in the referral process. Finally, the O (Outcome) component examines the impact of these constraints on the quality and accessibility of maternal health care. This scoping review employs many databases, including PubMed, ScienceDirect, Scopus, Springer, and Google Scholar, to identify papers using the phrases "maternal referral system," "barriers," "healthcare services," and "health outcomes." The study results suggested that six publications identified several impediments hindering women's access to hospital delivery facilities and maternal referral systems. The inclination towards home birth is shaped by diminished autonomy, economic reliance, and the impact of socio-cultural norms, especially among young women and vulnerable populations, who often disregard referral advisories despite elevated risks. Obstacles within the healthcare system including inadequate coordination among hospitals, insufficient comprehension of referral standards, limited training for healthcare professionals, and challenges related to political and information technology infrastructure. Additional significant obstacles include inadequate communication prior to referral, insufficient referral paperwork, and a scarcity of ambulances and qualified medical staff. Moreover, women encounter mobility limitations, delays in accessing care, and disrespectful treatment from healthcare providers. The maternal referral system aims to improve its efficacy, efficiency, and responsiveness, hence resulting in enhanced health outcomes for mothers and newborns and reducing maternal and neonatal death rates.